2010
DOI: 10.1021/cm101730f
|View full text |Cite
|
Sign up to set email alerts
|

NMR of Biopolymer-Apatite Composites: Developing a Model of the Molecular Structure of the Mineral-Matrix Interface in Calcium Phosphate Biomaterials

Abstract: Nanoparticulate hydroxyapatites (HAps) reproducing some of the subnanometre length scale intermolecular interactions characteristic of hard tissue have been prepared for nuclear magnetic resonance (NMR) structural elucidation. HAps were precipitated at physiological pH and temperature from dilute aqueous solutions, in the presence of acidic polysaccharides (chondroitin sulfate, dermatan sulfate, hyaluronic acid, dextran sulfate, polygalacturonic acid), and of hydrophilic poly aminoacids (poly-l-glutamate, poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Bradley et al prepared the hydroxyapatite composited with polysaccharides (such as chondroitin sulfate and polygalacturonic acid) or poly amino acid (like poly-L-asparagine and poly-L-lysine). 30 Gao et al reported that poly-3-lysine was introduced to the surface of bacterial cellulose nanobers via crosslinking for bone-like apatite deposition, and its nanocomposites were expected to be adapted for applications in bone tissue engineering. 31 Ding et al synthesised poly-L-lysine/HAp/carbon nanotube hybrid biocomposite scaffolds for antibody immobilisation.…”
Section: Introductionmentioning
confidence: 99%
“…Bradley et al prepared the hydroxyapatite composited with polysaccharides (such as chondroitin sulfate and polygalacturonic acid) or poly amino acid (like poly-L-asparagine and poly-L-lysine). 30 Gao et al reported that poly-3-lysine was introduced to the surface of bacterial cellulose nanobers via crosslinking for bone-like apatite deposition, and its nanocomposites were expected to be adapted for applications in bone tissue engineering. 31 Ding et al synthesised poly-L-lysine/HAp/carbon nanotube hybrid biocomposite scaffolds for antibody immobilisation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work on the mineral-matrix interface in calcium phosphate biomaterials shows how the NMR technique is versatile to unravel the complex intermolecular interactions in biological materials [17,18]. Proton NMR studies of collagen fibrils have led to recognize several types or water molecules in collagen.…”
Section: Discussionmentioning
confidence: 99%
“…All experiments were performed using standard SSNMR methodology on a Bruker 9.4 T Avance-400 spectrometer at frequencies of 400.1 ( 1 H), 161.9 ( 31 P) and 100.5 MHz ( 13 C) and at a magic angle spinning (MAS) rate of 12.5 kHz. Experimental parameters were essentially as previously described [23].…”
Section: Methodsmentioning
confidence: 99%